Contemporary Determinants of the Development of Socio-Economic Regions - Czyż, Teresa (Quaestiones Geographicae, 2014)
This article examines the effect on the development of socio-economic regions in Poland of contemporary external determinants considered at the European and the world scale. It consists of two parts. The first gives a description of the main general processes that are external determinants of regional development today: modernisation changes, globalisation, metropolitanisation, and European integration. Part two is empirical in character and seeks to find regional manifestations and effects of those determinants in Poland, and to establish how they influence regional income and spatial differences in its value.